Nuclear hnRNPA2B1 initiates and amplifies the innate immune response to DNA viruses - Wang, Lei; Wen, Mingyue; Cao, Xuetao (Science (American Association for the Advancement of Science), 2019)
DNA viruses typically eject genomic DNA into the nuclei of host cells after entry. It is unclear, however, how nuclear pathogen-derived DNA triggers innate immune responses. We report that heterogeneous nuclear ribonucleoprotein A2B1 (hnRNPA2B1) recognizes pathogenic DNA and amplifies interferon-α/β (IFN-α/β) production. Upon DNA virus infection, nuclear-localized hnRNPA2B1 senses viral DNA, homodimerizes, and is then demethylated at arginine-226 by the arginine demethylase JMJD6. This results in hnRNPA2B1 translocation to the cytoplasm where it activates the TANK-binding kinase 1-interferon regulatory factor 3 (TBK1-IRF3) pathway, leading to IFN-α/β production. Additionally, hnRNPA2B1 facilitates -methyladenosine (m A) modification and nucleocytoplasmic trafficking of , , and messenger RNAs. This, in turn, amplifies the activation of cytoplasmic TBK1-IRF3 mediated by these factors. Thus, hnRNPA2B1 plays important roles in initiating IFN-α/β production and enhancing stimulator of interferon genes (STING)-dependent cytoplasmic antiviral signaling.